Potential surfaces of the city of Colombo - Manawadu, L. (My University, 2013)
Potential Surface Analysis (PSA) is a method proposed by the Japanese International Cooperation Agency to identify the potential areas in a city for implementation of different social and economic activities. This method is almost similar to the Social Area Analysis (SAA), a theory and technique developed by two American Sociologists, Eshref Shevky and Wendell Bell (1955), linking changing urban social structure and residential patterns to economic development and urbanization processes. However, there were slight differences between Social Area Analysis and Potential Surface Analysis in terms of techniques proposed to analyse the data. This paper presents the procedures followed to conduct the Potential Surface Analysis as a case study of the city of Colombo, Sri Lanka and the results derived through the analysis